Evaluation of specific humoral and cellular immune responses against the major capsid L1 protein of cutaneous wart-associated alpha-Papillomaviruses in solid organ transplant recipients. Issue 1 (January 2015) - Gaiser, Maria R.; Textor, Sonja; Senger, Tilo; Schädlich, Lysann; Waterboer, Tim; Kaufmann, Andreas M.; Süsal, Caner; Pawlita, Michael; Enk, Alexander H.; Gissmann, Lutz; Lonsdorf, Anke S.
Highlights We analyzed HPV-specific immune responses in organ transplant recipients. Main cellular immune response against any HPV type was of TH1 type. Immune responses were higher in patients with common warts. Immune responses reflect individual level of iatrogenic immunosuppression.